Expectations of nursing undergraduates in relation to the job market and professional career - Laureano, Mikaeli de Lima (2022)
Objective: To identify the expectations of nursing students regarding the job market and professional career. Methodology: This is a descriptive and exploratory study, with a quantitative and qualitative approach, being carried out with nursing students from a private educational institution and analyzed using the content analysis technique. Results: Of the total of 103 possible surveyed, only 58 responded to the questionnaire, equivalent to 55.8% of the total, most of them middle class women, between 21 and 30 years old. It was possible to identify that 94.8% of the undergraduates wish to pursue a graduate degree and only 70.7% of the undergraduates consider themselves suitable for the job market. When asked about the intended area for action, we found in descending order of preference: Urgency and emergency, women's health, management, elderly health, child and adolescent health, intensive care unit, teaching and research, surgical center, collective health, neonatal and oncology. Conclusion: The student's expectations are to become a qualified and well-paid professional, and for this reason, he will continue to look for postgraduate, residency and master's courses, as he understands that he will be ready for the current job market that has become increasingly more demanding at the curricular level.